Attenuated Democracy A Critical Introduction to U.S. Government and Politics - Hubert, David (Open textbook library., 2020)
The U.S. political system suffers from endemic design flaws and is notable for the way that a small subset of Americans—whose interests often don’t align with those of the vast majority of the population—wields disproportionate power. Absent organized and persistent action on the part of ordinary Americans, the system tends to serve the already powerful. That’s why this text is called Attenuated Democracy. To attenuate something is to make it weak or thin. Democracy in America has been thin from the beginning and continues to be so despite some notable progress in voting rights. As political scientists Benjamin Page and Martin Gilens wrote, “The essence of democracy is not just having reasonably satisfactory policies; the essence of democracy is popular control of government, with each citizen having an equal voice.” (1) Since this is likely to be your only college-level course on the American political system, it is important to point out the structural weaknesses of our system and the thin nature of our democracy. Whenever you get the chance—in the voting booth, in your job, perhaps if you hold elected office—I encourage you to do something about America’s attenuated democracy.